2010
DOI: 10.1093/hmg/ddq361
|View full text |Cite
|
Sign up to set email alerts
|

A point mutation in the dynein heavy chain gene leads to striatal atrophy and compromises neurite outgrowth of striatal neurons

Abstract: The molecular motor dynein and its associated regulatory subunit dynactin have been implicated in several neurodegenerative conditions of the basal ganglia, such as Huntington's disease (HD) and Perry syndrome, an atypical Parkinson-like disease. This pathogenic role has been largely postulated from the existence of mutations in the dynactin subunit p150(Glued). However, dynactin is also able to act independently of dynein, and there is currently no direct evidence linking dynein to basal ganglia degeneration.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(48 citation statements)
references
References 63 publications
3
44
1
Order By: Relevance
“…Moreover, transgenic mice with a point mutation in the dynein heavy chain gene will also impair retrograde axonal transport and cause motor and behavioral abnormalities including hindlimb clasping, loss of muscle tone, and incoordination, which is accompanied by striatal atrophy and dystrophic neurites (5). These studies support a role for dynactin and dynein in the pathogenesis of neurodegenerative disorders.…”
Section: Gcase Inhibition Induced Synaptic Axonal Transport and Cytomentioning
confidence: 80%
“…Moreover, transgenic mice with a point mutation in the dynein heavy chain gene will also impair retrograde axonal transport and cause motor and behavioral abnormalities including hindlimb clasping, loss of muscle tone, and incoordination, which is accompanied by striatal atrophy and dystrophic neurites (5). These studies support a role for dynactin and dynein in the pathogenesis of neurodegenerative disorders.…”
Section: Gcase Inhibition Induced Synaptic Axonal Transport and Cytomentioning
confidence: 80%
“…The deficit in axonal transport includes mitochondria [64]. Finally, a point mutation in the dynein heavy chain leads to prominent striatal neurodegeneration, implying that MSNs are particularly sensitive to deficits in retrograde axonal transport [65]. Axonal transport has not been studied in regional HD models.…”
Section: )mentioning
confidence: 99%
“…Although very useful, they do not always reflect the clinical and pathological changes present in human subjects [37,38,40]. Many papers indicated that disorders in the intracellular transport might be crucial for the initiation or progression of motor neuron degeneration [35,41,42,43,44]. In our previous studies, we observed important changes in the expression of tau isoforms, kinesins and dynactin in various regions of the CNS obtained from autopsies of SALS patients and transgenic mice with symptoms of motor neuron degeneration [36,37,38,45].…”
Section: Discussionmentioning
confidence: 99%